Establishment and optimization of an evaluation index system for brownfield redevelopment projects: An empirical study. (December 2015) - Zhu, Yuming; Hipel, Keith W.; Ke, Ginger Y.; Chen, Ye
Abstract: Brownfield redevelopment has recently become the focus of attention of governments, communities, environmental advocates, scientists, and researchers around the world. The purpose of this study is to provide a framework for establishing and optimizing an evaluation index for brownfield redevelopment projects (BRPs). This framework involves three steps: the initial design, testing and optimization, and verification. With the help of two standard statistical software packages, the reliability and validity of the initialized index system are established, and then the optimization of the initial index system is carried out by means of Factor Analysis. The effectiveness of the optimization of the index system is verified through Structural Equation Modeling. Furthermore, an illustration example is used to show how to apply the established index system in the real world. Highlights: The paper develops an evaluation index system for brownfield redevelopment projects. The construction is based on an empirical study in China. Main procedure includes initial design, optimization, and verification. An illustration example is used to show the effectiveness and efficiency.